«Cosa bella mortal, passa, e non dura». L’enjeu esthétique de la vieillesse féminine à l’aube de l’époque moderne - Caroline Schuster Cordone (Storia delle Donne, 2006)
The present article focuses on the physical decline and the aesthetic dimension of feminine decrepitude at the beginning of Modern Times, trough images and statements of art theorists, artists and poets. The centre of our reflection is the aged and aging female body, which represented the absolute opposite to the existing renaissance discourse on feminine beauty. Confronted with the praise of an always admired youth, how did written and pictorial sources express the alteration due to feminine aging, and were there any ways to react to the effects of old age? Possible answers to these questions emerge through the analysis of images and texts facing the problem, as well as trough the study of the representation of the aging process itself, visible in images depicting a young woman at the mirror facing her aged reflection.